PREFERENSI DAN POLA KONSUMSI KONSUMEN SAYURAN ORGANIK DI SUPERINDO KEMILING BANDAR LAMPUNG - M Ikhwan Hidayatulloh; Yaktiworo Indriani; Rabiatul Adawiyah (Lampung University, 2026)
This research aimed to analyze consumer preferences and consumption patterns regarding organic vegetables at Superindo Kemiling Bandar Lampung City. This research utilized a descriptive quantitative approach through a survey method involving 50 housewife respondents who were selected purposively . Data analysis was conducted by the Fishbein multi-attribute model to measure consumer preferences and Rank Spearman correlation to examine correlations between research variables. Research results indicated that consumer preferences of organic vegetables were classified as very positive with a total attitude score (Ao) of 166.46. The leaf integrity attribute emerges as the main priority while parking area width was being the lowest score. Consumption pattern showed that the majority of respondents purchased 6 bundles of organic vegetables per month with stir-frying being the most common processing method. The primary reason for consumption was dominated by food safety (54%) and taste factors. Education, income, and family size have significant correlation to consumption patterns and the reasons for choosing vegetable processing methods. An increase in family size was proven to shift the primary consumer motivation from taste aspects toward considerations of time and energy efficiency as well as family traditions. This pattern demonstrated that larger household needed demand practical meal presentation without neglecting long-standing habitual values. Keywords: : consumer patterns, consumption preferences, organic vegetables